Shaddock - Hodge, W. (Stephens Ltd., Trinidad, 2009)
The shaddock is allied to the orange and the lemon and is presumably native to Malaysia and Polynesia. The name shaddock is said to have derived from that of a captain who introduced the tree to the West Indies.
Colour; Black and White; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Citrus maxima; Trees--Shaddock; Pummelo